印刷带线偶极子天线构成的天线阵列 (2023)
本发明提出一种印刷带线偶极子天线构成的天线阵列，包括：印刷带线偶极子天线，由介质基板上表面覆铜组成，其中位于该介质基板一侧表面的覆铜形成若干辐射部，位于该介质基板另一侧表面的覆铜形成若干馈电部，馈电部与辐射部一一对应组合配对；地板，与该印刷带线偶极子天线垂直设置，该印刷带线偶极子天线位于该地板的顶侧；馈电网络，设置在该地板的底侧；以及L形支撑架，用于将该印刷带线偶极子天线固定在该地板上组阵结构简单紧凑，通用性强易于实现，同时极大地降低了成本，适合大型相控阵天线。 The present invention provides an antenna array formed by printing strip line dipole antennas. The antenna array comprises: printing strip line dipole antennas formed by copper coating at the upper surface of a dielectric substrate, wherein coated copper located at the surface of one side of the dielectric substrate forms a plurality of radiation portions, the coated copper located at the surfaceat the other side of the dielectric substrate forms a plurality of feed portions, and the feed portions are in one-to-one correspondence combination and pairing with the radiation portions; a floor vertically arranged with the printing strip line dipole antennas which are located at the top side of the floor; a feed network arranged at the bottom side of the floor; and an L-shaped support